Dynamics of Resilience Formation in Single Parents Who Have Child with Special Needs - Antari, Ni Wayan Novi; Susilawati, Luh Kadek Pande Ary (Universitas Negeri Semarang, 2025)
Single parents with children with special needs face complex challenges that create social and psychological burdens, impacting their physical health and parenting styles. However, the resilience development process among single parents with children with special needs is not yet fully understood. This study aims to explore the dynamics of resilience development in single parents with children with special needs, enabling them to navigate these challenges. The method used was a literature review of various studies related to the process of resilience development in single parents. The results indicate four phases in resilience development: the surrender phase, the survival phase, the recovery phase, and the thriving phase. In the surrender phase, parents feel overwhelmed by the situation they are facing. The survival phase is characterized by efforts to meet their child's and their own basic needs despite limitations. In the recovery phase, parents begin to accept their child's condition and develop more adaptive parenting strategies. The thriving phase demonstrates the ability of parents to find meaning, enhance their capacity, and support optimal child development. This study emphasizes the importance of resilience development in single parents with children with special needs to prevent psychological problems and improve family well-being. The implication of these findings is the need for psychosocial support and empowerment of single parents in community-based intervention programs to strengthen their resilience in facing various parenting challenges.